1997
DOI: 10.1017/s1357729800015836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the β-adrenergic agonist cimaterol and dietary protein level on fat young sheep given diets containing submaintenance levels of dietary energy

Abstract: Thirty Suffolk cross wether sheep aged about 12 months and weighing 57 kg on average were used. They had been given previously a high energy diet to produce a fat body condition and average condition score of 3-7. Animals 'were allocated to an initial slaughter group (IS) or to four dietary treatment groups (UL, UH, CL and CH) based on sugar-beet feed (L) or white-fish meal (H) supplemented with chopped straw and pelleted, without (UL and UH) or with (CL and CH) the (5-adrenergic agonist cimaterol, to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…Ortigues et al (1990) measured comparable effects of fish meal supplementation on BUN levels in heifers under a similar regimen. Galbraith et al (1997) found a difference in BUN between fish meal supplemented and unsupplemented treatments similar to that observed in the present study. Lindberg and Jacobsson (1990) found significant effects on BUN levels of both energy and N concentration of intragastric infusates in lambs of comparable age and size.…”
Section: Metabolitessupporting
confidence: 91%
See 3 more Smart Citations
“…Ortigues et al (1990) measured comparable effects of fish meal supplementation on BUN levels in heifers under a similar regimen. Galbraith et al (1997) found a difference in BUN between fish meal supplemented and unsupplemented treatments similar to that observed in the present study. Lindberg and Jacobsson (1990) found significant effects on BUN levels of both energy and N concentration of intragastric infusates in lambs of comparable age and size.…”
Section: Metabolitessupporting
confidence: 91%
“…These observations do not support an enhanced use of endogenous fuels for protein accretion under high N supply. In a similar experiment, Galbraith et al (1997) did not find enhanced protein accretion in lambs, but rather a tendency toward lower peripheral fat mass and higher carcass fat losses for N supplemented growing lambs, compared to unsupplemented lambs.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In nonruminant species, zilpaterol increased plasma glucose levels within 72 h, but significantly decreased glucose levels after 14 days (20). As in the present study, Galbraith et al (21) recorded significant reductions in plasma-free fatty acids at day 9, but observed an increase in plasma glucose concentration at day 49 in lambs treated with cimaterol. Likewise, Kim et al (22) observed significant increases in the plasma concentrations of fatty acids and triglycerides following supplementation with 10 ppm of cimaterol.…”
Section: Concentration Of Plasma Metabolitessupporting
confidence: 79%